ASSESSMENT OF PREGNANCY MANAGEMENT AND OUTCOMES AMONG PRIMIGRAVID WOMEN AT DONG NAI-2 HOSPITAL (Tạp chí Y học Cộng đồng, 2026)
Objective: This study aimed to evaluate antenatal care practices, pregnancy abnormalities, and birth outcomes, and to identify associated factors among primigravid women.Subjects and methods: A prospective longitudinal observational study  was conducted to evaluate antenatal care, pregnancy abnormalities, birth outcomes, and associated factors among primigravid women managed at Dong Nai-2 Hospital from June 2025 to February 2026.Results: Of 202 participants, 15 (7.4%) experienced miscarriage, leaving 187 women followed throughout pregnancy. All underwent prenatal screening, and 99.5% completed tetanus vaccination. Antenatal care was initiated early, with 50.5% at 8-12 weeks and 48.5% before 8 weeks, and a mean of 13.7 visits. Pregnancy abnormalities occurred in 44.6%, most commonly gestational diabetes mellitus (24.8%) and prelabor rupture of membranes (17.3%). Cesarean section was the predominant mode of delivery (57.8%), mainly due to cephalopelvic disproportion (30.5%) and arrest of labor (13.4%). Neonatal outcomes were generally favorable, including low birth weight (5.9%), preterm birth (3.7%), and respiratory distress (0.5%), with unfavorable outcomes in 21.9%. In multivariable analysis, maternal age 25-34 years and rural residence were associated with higher odds of pregnancy abnormalities, whereas a first antenatal visit before 8 weeks was associated with lower odds. A higher number of antenatal visits was associated with reduced odds of unfavorable outcomes (aOR = 0.84, 95% CI: 0.77-0.91), while pregnancy abnormalities increased this risk (aOR = 3.15, 95% CI: 1.53-6.49).Conclusion: Despite generally adequate antenatal care, pregnancy abnormalities remained common and were the main determinant of adverse outcomes, underscoring the importance of early and continuous monitoring.
Keywords: pregnancy outcome, pregnant women, primigravid, pregnancy management.